TVGG Dental Implant Identification System - Guo, Jianbin; Tsai, Pei-Wei; Xue, Xingsi; Wu, Dong; Van, Qui Tran; Kaluarachchi, Chanaka Nimantha; Dang, Hong Thi; Chintha, Nikhitha (Frontiers in Pharmacology, 2022)
Identifying the right accessories for installing the dental implant is a vital element that impacts the sustainability and the reliability of the dental prosthesis when the medical case of a patient is not comprehensive. Dentists need to identify the implant manufacturer from the x-ray image to determine further treatment procedures. Identifying the manufacturer is a high-pressure task under the scaling volume of patients pending in the queue for treatment. To reduce the burden on the doctors, a dental implant identification system is built based on a new proposed thinner VGG model with an on-demand client-server structure. We propose a thinner version of VGG16 called TVGG by reducing the number of neurons in the dense layers to improve the system's performance and gain advantages from the limited texture and patterns in the dental radiography images. The outcome of the proposed system is compared with the original pre-trained VGG16 to verify the usability of the proposed system.